Surface coated cutting tools
By employing a hard coating layer with specific residual stress management on the substrate, the surface-coated cutting tool achieves superior wear resistance and fracture resistance, addressing the limitations of existing tools in long-term use and intermittent cutting.
Patent Information
- Application Number
- JP2021033721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-03-03
AI Technical Summary
Existing surface-coated cutting tools face challenges in achieving both excellent wear resistance and defect resistance, especially during long-term use and intermittent cutting of difficult-to-cut materials.
The surface-coated cutting tool features a hard coating layer with a lower Ti nitride or carbonitride layer and an upper AlTi composite nitride or carbonitride layer, applied using chemical vapor deposition. The tool substrate undergoes pretreatment or post-treatment with wet blasting or dry crust to intentionally apply residual stress, optimizing the stress difference between the rake and flank surfaces to enhance fracture resistance without compromising wear resistance.
This approach results in a cutting tool with improved wear resistance, fracture resistance, and defect resistance, enabling extended tool life and enhanced performance in both continuous high-speed cutting and intermittent cutting processes.
Smart Images

Figure 0007649467000010 
Figure 0007649467000001 
Figure 0007649467000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-coated cutting tool (hereinafter sometimes simply referred to as a "coated tool") that exhibits excellent cutting performance not only in continuous high-speed cutting but also in intermittent cutting by virtue of the fact that its hard coating layer has excellent chipping resistance and wear resistance. [Background technology]
[0002] In cutting difficult-to-cut materials such as stainless steel, steels with remaining cut surfaces, and nickel-based heat-resistant alloys, cutting tools coated with AlTiN by the CVD method are known to exhibit high wear resistance in continuous high-speed cutting due to the hardness and oxidation resistance of the coating. On the other hand, when the workpiece is a difficult-to-cut material such as stainless steel or nickel-based heat-resistant alloy, which has high toughness, or when cutting an unstable cutting surface where the cutting depth varies, or when cutting in a cutting region with high intermittency, the high hardness of the coating causes significant particle fall-off, leading to the progression of abnormal damage including tool breakage, and the original performance cannot be demonstrated.
[0003] In contrast, for example, Patent Document 1 describes a hard coating layer formed on a substrate surface by chemical vapor deposition that is made of a composite nitride (TiAlN) layer of Ti and Al or a composite carbonitride (TiAlCN) layer, has a face-centered cubic structure of at least 90 volume %, has a maximum orientation index TC(111) in the (111) plane when subjected to X-ray diffraction and is at least 1.5, and has a residual stress value of 0 MPa or less and -5000 MPa or more in a residual compression state, whereby improved crack resistance and wear resistance as a tool are observed. In addition, the orientation index TC(111) of the (111) plane was derived using the measured X-ray diffraction peak intensities for each of the (111), (200), (220), and (311) crystal planes of the Ti and Al complex carbonitride.
[0004] In Patent Document 2, in a surface-coated cutting tool having a rake face and a flank face, with the boundary portion between them forming a cutting edge, a TiAlN layer having a NaCl-type crystal structure with a specific composition, formed on the surface of a substrate by chemical vapor deposition (CVD), exhibits a maximum orientation index TC(111) on the (111) plane, and when the value satisfies 1.0 < TC(111) ≤ 4.0, a surface-coated cutting tool that exhibits excellent wear resistance and chipping resistance is obtained, as described. Here, in deriving the orientation index TC(111) of the (111) plane, the measured values of the X-ray diffraction peak intensities for the (111), (200), (220), (311), and (222) crystal planes, which are the crystal growth preferred orientations of the Ti, Al composite carbonitride, are used.
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0006] In recent years, demands for labor saving and energy saving in cutting processes have been strong. Along with this, cutting processes tend to be faster and more efficient. In coated tools, due to the occurrence of particle detachment, abnormal damage accompanied by tool chipping occurs, so excellent chipping resistance is required. Furthermore, for long-term use, excellent wear resistance is required. In Patent Documents 1 and 2, in a coated tool, by orienting the crystal planes of the crystal grains of an Al, Ti composite carbonitride having a cubic crystal structure, formed as a hard coating layer using chemical vapor deposition, to the (111) plane, a coated tool having both excellent chipping resistance and wear resistance has been proposed. However, simply orienting the crystal planes of the crystal grains of an Al, Ti composite carbonitride having a NaCl-type crystal structure of a specific composition to the (111) plane and specifying the orientation index within a specific range improves fracture resistance but reduces wear resistance. This means that it is not possible to achieve both fracture resistance and wear resistance, and as a result, there is a problem in that long-term use cannot be realized.
[0007] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has an object to solve the above problems and to provide a surface-coated cutting tool which has excellent wear resistance and high chipping resistance without early wear damage even when used for a long period of time. [Means for solving the problem]
[0008] From the above viewpoints, the present inventors have conducted intensive research in order to achieve an improvement in both fracture resistance and wear resistance of a coated tool having a hard coating layer made of an Al-Ti composite carbonitride formed by chemical vapor deposition, and as a result, have obtained the following findings.
[0009] That is, the inventors have discovered that, when forming a lower layer of a hard coating made of CVD-AlTiN on a tungsten carbide-based cemented carbide substrate, for example, by performing a pretreatment such as wet blasting or dry blasting on the cutting edge rake face of the substrate, or by performing wet blasting or dry blasting as a post-treatment after the formation of the hard coating layer, or by performing both, it is possible to intentionally impart appropriate values of residual stress to each of the cutting edge rake face and flank face of the substrate, thereby obtaining a surface-coated cutting tool with excellent chipping resistance without reducing wear resistance.
[0010] Specifically, the residual stress S2 on the cutting edge rake face of the tungsten carbide based cemented carbide substrate of the surface-coated tool is set to a value smaller than the residual stress S1 on the cutting edge flank face (S1>S2), and a residual stress of at least -200 MPa or less (S2≦-200 MPa) is imparted. The residual stress S1 on the cutting edge flank face of the substrate is set to a value larger than the residual stress S2 (S1>S2), and the absolute value of the difference between S1 and S2 is set to 250MPa More preferably, the residual stress S2 on the cutting edge rake face is set to a residual stress of -850 MPa or less (S2≦-850 MPa), i.e., a residual compressive stress of 850 MPa or more, and the residual stress S1 on the cutting edge flank face of the base body is set to a value greater than S2 (S1>S2), and the absolute value of the difference between S1 and S2 is set to 500. MPa This was made on the basis of the finding that by setting the value to a larger value, a surface-coated cutting tool having excellent chipping resistance without decreasing wear resistance and particularly suitable for turning can be obtained. Here, when the residual stress S2 on the cutting edge rake face is, for example, "-200 MPa", it means that the residual stress S2 is a residual compressive stress and the residual compressive stress value is 200 MPa, and when "S2≦-200 MPa" it means that "the residual stress S2 is -200 MPa or less", that is, "the residual compressive stress S2 is 200 MPa or more". The same is true for the residual stress S1 on the cutting edge flank.
[0011] The present invention has been made based on the above findings, "(1) A surface-coated cutting tool having a hard coating layer on the surface of a tool substrate made of a tungsten carbide-based cemented carbide, (a) the hard coating layer has at least two layers, a lower layer directly contacting the outermost surface of the tool substrate and an upper layer directly contacting the lower layer, and the total average thickness of the hard coating layer is 0.6 to 21.0 μm; (b) the lower layer is made of a Ti nitride or carbonitride and has an average layer thickness of 0.05 to 2.0 μm; (c) The upper layer is a composite nitride of Al and Ti. layer or Composite carbonitride layer and the average layer thickness is 0.5 to 20.0 μm; Composition formula: (Al X Ti 1-X )(C Y N 1-Y), the average content ratio X of Al to the total amount of Ti and Al in the composite nitride layer or the composite carbonitride layer is avg and the composite nitride layer Or the average content ratio Y of C to the total amount of C and N in the composite carbonitride layer avg (However, X avg , Y avg are atomic ratios), respectively, 0.70≦X avg ≦0.90, 0≦Y avg <0.05 and is made of a composite nitride layer or a composite carbonitride layer having a NaCl type face-centered cubic structure, (d) When the residual stress on the cutting edge flank of the tungsten carbide based cemented carbide of the surface-coated tool is S1 and the residual stress on the cutting edge rake face is S2, α)S1>S2 β)S2≦-200MPa γ) The absolute value of the difference between S1 and S2 is greater than 250 MPa Surface coated cutting tools that meet the requirements. (2) When X-ray diffraction is performed on the upper layer, the ratio of the diffraction intensity value of the cubic (200) plane to the diffraction intensity value of the cubic (111) plane, I(111) / I(200), is 2. The surface-coated cutting tool according to claim 1, wherein the relationship I(111) / I(200) is satisfied. (3) When the residual stress on the cutting edge flank of the tungsten carbide-based cemented carbide of the surface-coated tool is S1 and the residual stress on the cutting edge rake face is S2, α)S1>S2 β)S2≦-850MPa γ) The absolute value of the difference between S1 and S2 is greater than 500 MPa A surface-coated cutting tool according to (1) or (2), which satisfies the above requirements. It is characterized by the following. In this specification, when a numerical range is indicated using "~" or "-", it means that the lower and upper limits of the numerical range are included. Next, the tool substrate and the hard coating layer of the coated tool of the present invention will be specifically described.
[0012] 1. Tool base; The tool substrate is made of a tungsten carbide-based cemented carbide. In the present invention, a residual stress of -200 MPa or less, more preferably -850 MPa or less is imparted to the cutting edge rake face of the cemented carbide substrate, thereby increasing adhesion with the hard coating layer, and the tool can be used as a cutting tool having excellent cutting performance in terms of chipping resistance and wear resistance not only in the continuous high-speed cutting region but also in the intermittent cutting region. Furthermore, by setting the residual stress value on the cutting edge rake face of the alloy substrate to -200 MPa or less, more preferably -850 MPa or less, it is possible to suppress the development of cracks during machining and to exhibit high chipping resistance. On the other hand, when the compressive residual stress increases on the flank as on the cutting face and the absolute value of the difference between the residual stress value on the rake face and the residual stress value on the flank falls below 250 MPa, coating peeling is likely to occur starting from the tool flank during plastic deformation of the base material. Therefore, it is necessary that the absolute value of the difference between the residual stress value on the rake face and the residual stress value on the flank be greater than 250 MPa, and preferably greater than 500 MPa. The residual stress can be imparted to the tool substrate by wet blasting or dry blasting as a pretreatment before the formation of a hard coating layer described later, or as a posttreatment after the formation of a hard coating layer described later. When wet blasting or dry blasting is performed as a pretreatment prior to the formation of a hard coating layer, the film formation temperature can be set lower than usual to suppress relaxation of residual stress, thereby extending the life of the tool. For example, the application of residual stress to the substrate by blasting is carried out by projecting a dry or wet blasting treatment onto the tool surface using media containing alumina, silicon nitride, or zirconia abrasive grains before or after the formation of a hard coating layer. Blasting conditions; Abrasive grains: ZrO2 grains, Al2O3 grains Grain shape: spherical and / or polygonal Grain size (particle size): 125-425μm (spherical) / <125μm (polygonal) Blasting pressure: 0.1-0.4MPa Blast projected at 70~90° from the rake face Projection time: 4-16 seconds
[0013] 2.Hard coating layer; The hardcoat layer comprises a bottom layer and a top layer, and further layers may include a top layer disposed on the top layer. The average thickness of the hard coating layer is set to 0.6 μm or more because adhesion, wear resistance, and chipping resistance cannot be sufficiently ensured over a long period of use if it is less than 0.6 μm. On the other hand, if the average thickness exceeds 21.0 μm, peeling or chipping is likely to occur, so it is preferable to set the average thickness to 21.0 μm or less.
[0014] (a) lower layer; <Average layer thickness> The lower layer is made of Ti nitride or carbonitride and is provided directly on the tool substrate. The average thickness of the lower layer is set to 0.05 μm or more because sufficient adhesion cannot be obtained if the average thickness is less than 0.05 μm. On the other hand, if the average thickness exceeds 2.0 μm, the deformation of the obtained hard coating layer becomes significant and peeling from the tool substrate occurs easily in the early stage of cutting, so the average thickness is set to 2.0 μm or less.
[0015] <Component composition> The composition of the lower layer is not particularly limited as long as it is a nitride or carbonitride of Ti, since it does not impede the object of the present invention. For example, the composition formula is TiC Z N 1-Z When expressed as above, the range of 0≦Z≦0.05 is preferable. That is, if Z is contained in an amount greater than 0.05, the hardness of the lower layer increases excessively, and peeling from the interface between the lower layer and the substrate becomes more likely to occur.
[0016] (b) Upper layer <Average layer thickness> The upper layer is made of a composite nitride or composite carbonitride of Ti and Al, and is provided directly on and in contact with the lower layer. If the average thickness of the upper layer is less than 0.5 μm, the hard layer in the entire coating is insufficient and the wear resistance is poor, so the average thickness is set to 0.5 μm or more. On the other hand, if the average thickness exceeds 20.0 μm, the hard layer becomes too thick and peeling or chipping occurs easily during processing, so the average thickness is set to 20.0 μm or less.
[0017] <Component composition> The upper layer is composed of an Al and Ti composite nitride layer (AlTiN layer) or a composite carbonitride layer (AlTiCN layer), and exhibits uniform wear resistance and toughness throughout the entire layer. The Ti component improves high-temperature strength, while the Al component complements high-temperature hardness and heat resistance, so that a low wear coefficient is maintained even under high-temperature cutting conditions, and excellent heat resistance can be demonstrated. The composite nitride or composite carbonitride constituting the Al, Ti composite nitride layer or composite carbonitride layer is specifically represented by the composition formula: (Al X Ti 1-X )(C Y N 1-Y ), but the average Al content X avg If the value of X (atomic ratio) is less than 0.70, the high-temperature hardness is insufficient and the wear resistance decreases. avg When the (atomic ratio) value exceeds 0.90, the relative Ti content decreases, and the (Al X Ti 1-X )(C Y N 1-Y ) The high-temperature strength of the layer itself decreases, making it more susceptible to chipping and fracture. Therefore, the average Al content ratio X avg The value of (atomic ratio) is set to be in the range of 0.70 to 0.90, which is close to the maximum hardness and provides a particularly high effect. In addition, the C component has the effect of improving hardness, but the average content ratio Y avg If the atomic ratio is 0.05 or more, the high-temperature strength decreases, so the average content ratio Y avg (Atomic ratio) is 0≦Y avg It was defined as <0.05.
[0018] <Crystal orientation> The upper layer is made of Al, Ti composite nitride or composite carbonitride (Al X Ti 1-X )(C Y N 1-Y ) can improve the hardness by adopting a NaCl-type face-centered cubic structure (hereinafter sometimes simply referred to as a "cubic structure"). That is, by forming an Al-Ti composite nitride layer or composite carbonitride layer having a high orientation to the (111) plane of a cubic crystal structure, it is possible to increase the hardness. In addition, when the ratio I(111) / I(200) of the diffraction intensity value I(200) of the (111) plane to the diffraction intensity value I(111) of the (200) plane in the upper layer is 1.0 or more, crystal grains are less likely to fall off during processing, so it is desirable to make I(111) / I(200)≧1.0.
[0019] (c)Top layer In the present invention, a top layer can be provided on the AlTi composite nitride layer or the AlTi composite carbonitride layer, which is the upper layer, as necessary, from the viewpoint of improving wear resistance and responding to a wider range of processing applications. Specifically, a layer made of an Al oxide such as α-Al2O3 or κ-Al2O3, or a Ti nitride layer or carbonitride layer can be provided within the range of 4.5 μm or less.
[0020] 3. Method for forming hard coating layer; (a) Method of imparting residual stress to a tool base Residual stress can be imparted to the tool substrate by blasting (wet blasting or dry blasting) as a pretreatment before the formation of the hard coating layer described below, or as a posttreatment after the formation of the hard coating layer. When the blast treatment is performed as a pretreatment before the formation of a hard coating layer described later, the film formation temperature can be set lower than the conventional treatment temperature to suppress the tensile stress of the hard coating layer, thereby making it possible to extend the life of the cutting tool.
[0021] (b) Method for forming the lower layer The lower layer of the hard coating layer is composed of a compound layer consisting of Ti and nitrogen, or a compound layer consisting of Ti, nitrogen, and carbon. In the first step, a chemical vapor deposition method is used to form a TiN layer or TiCN layer with excellent adhesion by adjusting the reaction gas composition (gas group A) and the reaction atmosphere such as pressure and temperature within appropriate ranges for each compound layer to be formed. [Deposition conditions] 1)TiN layer; Processing method: Deposition using CVD Reactant gas composition (volume %) TiCl4: 3.0~6.0%, N2: 25.0~35.0%, H2: remainder, Reaction atmosphere pressure: 4.0 to 12.0 kPa, Reaction atmosphere temperature: 780~900℃ 2)TiCN layer; Processing method: Deposition using CVD Reactant gas composition (volume %) TiCl4:3.0~6.0%, N2:15.0~30.0%, CH4 or CH3CN: 0.6-2.0%, H2: balance Reaction atmosphere pressure: 7.0 to 12.0 kPa, Reaction atmosphere temperature: 780~900℃
[0022] (c) Method for forming the upper layer Next, in the method for forming the upper layer according to the present invention, the conditions for forming the AlTi composite nitride layer or the AlTi composite carbonitride layer are, for example, to use two types of NH3 gas having different heating temperatures, and the high-temperature ammonia gas can be used to suppress nucleation and promote crystallization, thereby obtaining coarse grains. That is, the method for forming an AlTiN or AlTiCN layer according to the present invention forms a film by alternately repeating the second step (initial nucleus formation step), i.e., the step of forming AlTiN crystals or AlTiCN crystals that serve as initial nuclei for forming an AlTiN or AlTiCN film, and the third step (crystal growth step), i.e., the step of growing the AlTiN crystals or AlTiCN crystals that serve as initial nuclei to form an AlTiN or AlTiCN film. The film formation conditions for each film formation step are outlined below. In particular, in the second step, which is the step of forming the initial nuclei of fine AlTiN or AlTiCN crystals, the following gas group B and gas group C are alternately supplied to the reactor with a phase difference to form a film, and ammonia gas preheated to a high temperature (e.g., 300 to 450°C) is used to promote nucleation. In the subsequent third step, the following gas group D and gas group E are alternately supplied to the reactor with a phase difference to form a film, and the ammonia gas used is changed to ammonia gas preheated to a low temperature (e.g., 50 to 250°C), which suppresses nucleation and promotes crystallization, and allows the desired crystals to be obtained. The number of times the second and third steps are repeated is adjusted according to the target film thickness.
[0023] [Deposition conditions] 1) Second step (initial nucleation step) Processing method: Deposition using CVD method Reactant gas composition (volume %): Gas group B: TiCl4: 0.01-0.04%, AlCl3: 0.01-0.05%, N2: 0~10%, C2H4: 0~0.5%, H2: remaining Gas group C: NH3: 0.1-0.8%, H2: 25.0-35.0%, Reaction atmosphere pressure: 4.0~5.0kPa, Reaction atmosphere temperature: 700~850℃ Supply cycle: 1~5 seconds, Gas supply time per cycle: 0.15 to 0.25 seconds, Phase difference between gas group B supply and gas group C supply: 0.10 to 0.20 seconds Gas group C preheat temperature: 300~450℃
[0024] 2) 3rd process (crystal growth process) Processing method: Deposition using CVD method Reactant gas composition (volume %): Gas group D: TiCl4: 0.01-0.04%, AlCl3: 0.01-0.05%, N2: 0~10%, C2H4: 0~0.5%, H2: remainder, Gas group E: NH3: 0.1-0.8%, H2: 25.0-35.0%, Reaction atmosphere pressure: 4.0~5.0kPa, Reaction atmosphere temperature: 700~850℃ Supply cycle: 1~5 seconds, Gas supply time per cycle: 0.15 to 0.25 seconds, Phase difference between gas group D supply and gas group E supply: 0.10 to 0.20 seconds Preheat temperature for gas group E: 50 to 250°C In addition, the volume percentage of each gas component in the reaction gas composition (volume percentage) in each of the second and third steps indicates the volume percentage of each component calculated with the sum of Gas Group B and Gas Group C being 100 volume % in the second step, and indicates the volume percentage of each component calculated with the sum of Gas Group D and Gas Group E being 100 volume % in the third step. Effect of the Invention
[0025] The surface-coated cutting tool of the present invention imparts a predetermined range of residual stress to each of the rake face and flank face of the tool base, thereby maintaining the wear resistance of the hard coating layer during cutting, enhancing the peeling resistance, suppressing the progression of cracks, and exhibiting resistance to fracture and chipping, thereby improving the tool life. In particular, in turning, defects occur due to the progression of cracks from the cutting face to the flank, so a significant effect of suppressing the progression of cracks can be achieved by keeping the residual stress on the cutting face at -200 MPa or less, i.e., under high compressive residual stress. On the other hand, as with the cutting face, compressive residual stress increases on the flank face, and if the absolute value of the difference between the residual stress value on the rake face and the residual stress value on the flank face falls below 250 MPa, coating peeling becomes more likely to occur during plastic deformation of the base material. Therefore, it is necessary that the absolute value of the difference between the residual stress value on the rake face and the residual stress value on the flank face be greater than 250 MPa. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a schematic cross-sectional view showing the relationship between a tool substrate of a coated tool according to the present invention and a lower layer (Ti(C)N layer), an upper layer (CVD-AlTiN(C) layer), and a top layer constituting a hard coating layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Next, the coated tool of the present invention will be specifically described with reference to examples. EXAMPLES
[0028] As raw material powders, WC powder, TiC powder, TaC powder, NbC powder, Cr3C2 powder and Co powder, all having an average particle size of 1 to 3 μm, were prepared. These raw material powders were mixed according to the composition shown in Table 1, wax was added, and the mixture was mixed in a ball mill in acetone for 24 hours. After drying under reduced pressure, the mixture was pressed into a green compact of a predetermined shape at a pressure of 98 MPa. This green compact was vacuum sintered in a vacuum of 5 Pa at a predetermined temperature in the range of 1370 to 1470°C for 1 hour. After sintering, tool substrates A to C made of WC-based cemented carbide having an insert shape according to ISO standard DNMG150408 were produced, respectively.
[0029] Next, each of these tool substrates A to C was placed in a chemical vapor deposition apparatus, and coated tools 1 to 8 of the present invention were produced, respectively, according to the following procedure. As described above, in the present invention, it is assumed that the cutting faces of the tool substrates A to C are subjected to blasting treatment as a pretreatment before the formation of the hard coating layer and / or a posttreatment after the formation of the hard coating layer, thereby imparting residual stress to the cutting face and flank face of the substrate (see Table 2). Next, in the first step, one of the tool substrates A to C is placed in a chemical vapor deposition apparatus, and film formation is performed for a certain period of time under the temperature and pressure conditions described in the formation conditions (formation symbols) A to H shown in Table 3 using gas group A (TiCl4, N2, CH4, CH3CN, and the remainder H2) having the component composition shown in Table 3.
[0030] For the coated tools 1 to 5 of the present invention, following the first step, in the second step (upper layer initial nucleus formation step), film formation was carried out for a certain period of time based on the gas composition, supply conditions, and gas reaction conditions (pressure, temperature, process time (seconds)) of gas group B and gas group C described in the formation conditions (formation symbols) A to E shown in Table 4, and in the third step (upper layer crystal growth step), film formation was carried out for a certain period of time based on the gas composition, supply conditions, and gas reaction conditions (pressure, temperature, process time (seconds)) of gas group D and gas group E described in the formation conditions (formation symbols) A to E shown in Table 5, to obtain the coated tools 1 to 5 of the present invention shown in Table 7. In addition, for coated tools 6 to 8 of the present invention, following the first step (lower layer deposition step), in the second step (upper layer initial nucleus formation step), deposition was performed under the deposition conditions (deposition symbols) F to H shown in Table 4, and in the third step (upper layer crystal growth step), deposition was performed under the deposition conditions (deposition symbols) F to H shown in Table 5. Furthermore, as the top layer, a κ-Al2O3 layer, an l-TiCN layer or an α-Al2O3 layer was deposited under the deposition conditions shown in Table 6, thereby obtaining coated tools 6 to 8 of the present invention shown in Table 7.
[0031] For the purpose of comparison, comparative coated tools 1 to 5 were formed under the forming conditions (forming symbols) a to e shown in Tables 3, 4 and 5, and comparative coated tools 1 to 5 shown in Table 8 were obtained. For comparative coated tools 6 to 8, coatings were formed under the forming conditions (forming symbols) f to h shown in Tables 3, 4 and 5, and then a κ-Al2O3 layer, an l-TiCN layer or an α-Al2O3 layer was formed as the uppermost layer under the forming conditions (forming symbols) shown in Table 6, thereby obtaining comparative coated tools 6 to 8 shown in Table 8.
[0032] Table 7 shows the residual stress values of the flank and rake faces of the tool substrates of the coated tools 1 to 8 of the present invention, the target average total thickness of the hard coating layer, the target average thickness and type of film formed of the lower layer, the target average thickness of the upper layer, the average Al content (Xavg), the average C content (Yavg), the crystal structure and diffraction line intensity ratio (I(111) / I(200)), and the target average thickness and film formed of the top layer. Similarly, Table 8 shows the residual stresses on the flank and rake faces of the tool substrate, the target average total thickness of the hard coating layer, the target average thickness and type of coating of the lower layer, the target average thickness of the upper layer, the average Al content (Xavg), the average C content (Yavg), the crystal structure and diffraction line intensity ratio (I(111) / I(200)), and the target average thickness of the top layer for the comparative coated tools 1 to 8.
[0033] Here, the thickness of the hard coating layer of the coated tools 1 to 8 of the present invention and the comparative coated tools 1 to 8 was measured using a scanning electron microscope (magnification: 5000 times). That is, the tool base was polished so that a cross section perpendicular to the substrate was exposed, and each layer was observed at a magnification of 5,000 to 20,000 times. The layer thicknesses were measured at five points within the observed field of view, and the average value was taken as the average layer thickness. The average layer thickness is shown in Table 7 for coated tools 1 to 8 of the present invention, and in Table 8 for comparative coated tools 1 to 8. In addition, the average Al content of the upper layer of AlTiN or AlTiCN is X avg (atomic ratio) and the average content ratio Y of C component avg The atomic ratio was determined by irradiating a polished surface of a sample with an electron beam from the surface side of the sample using an electron probe microanalyser (EPMA), and averaging the 10-point analysis results of the characteristic X-rays obtained. The coated tools 1 to 8 of the present invention are shown in Table 7, the comparative coated tools 1 to 8 are shown in Table 8, and avg and Y avg Indicates the value of.
[0034] The crystal structures of the AlTiN layer and the AlTiCN layer in the upper layers of the hard coating layer of the coated tool of the present invention and the comparative coated tool can be confirmed by performing X-ray diffraction on the surface of the hard coating layer parallel to the tool substrate surface, for example, using an X-ray diffractometer with Cu-Kα radiation as the radiation source under conditions of a measurement range (2θ): 20 to 120 degrees, a scan step: 0.013 degrees, and a measurement time per step: 0.48 sec / step, and by observing X-ray diffraction peaks that appear between the diffraction angles of the same crystal planes shown in JCPDS00-038-1420 cubic TiN and JCPDS00-046-1200 cubic AlN (for example, 36.66 to 38.53°, 43.59 to 44.77°, 61.81 to 65.18°). In addition, from the measured X-ray diffraction peak intensities I(hkl) for the (200) and (111) planes, the ratio of the diffraction peak intensity I(111) for the (111) plane to the diffraction peak intensity I(200) for the (200) plane, I(111) / I(200), can be obtained. The residual stress in the tool base is sin 2 The measurements are performed using the Ψ method with an X-ray diffractometer using Cu κα. The measurements are performed using the diffraction peak of the WC(211) plane, with a Young's modulus of 534 GPa and a Poisson's ratio of 0.22.
[0035] [Table 1]
[0036] [Table 2]
[0037] [Table 3]
[0038] [Table 4]
[0039] [Table 5]
[0040] [Table 6]
[0041] [Table 7]
[0042] [Table 8]
[0043] Next, with each of the various coated tools clamped to the tip of a tool steel cutter using a fixing jig, wet intermittent cutting tests of Inconel were carried out for the coated tools 1 to 8 of the present invention and the comparative coated tools 1 to 8, as shown below, and the maximum machining time until tool chipping was evaluated. The results are shown in Table 9.
[0044] ≪Cutting conditions≫ Cutting test: Wet turning, intermittent cutting Work material: Inconel 718 slit material Outer diameter 200mm, length 400mm (grooved round bar material) (4mm wide slits are spaced at equal intervals of 50mm) Rotation speed: 80 min -1 , Cutting speed: 50m / sec. Cutting depth: 0.5mm, Feed per blade: 0.6mm / rev Cutting time: Processing until the cutting edge is chipped
[0045] [Table 9]
[0046] As is clear from the cutting test results shown in Table 9, The coated tool of the present invention exhibits excellent chipping resistance and wear resistance over a long period of time. [Industrial Applicability]
[0047] As described above, the surface-coated cutting tool of the present invention exhibits excellent wear resistance, fracture resistance and chipping resistance not only when used in continuous cutting or intermittent cutting of ordinary steels, but also when used in intermittent cutting of difficult-to-cut materials such as stainless steel, steels with remaining fused surfaces, or nickel alloys, and therefore fully satisfies the needs for high performance cutting equipment, labor-saving and energy-saving cutting, and cost reduction.
Claims
1. A surface-coated cutting tool having a hard coating layer on a surface of a tool substrate made of a tungsten carbide-based cemented carbide, (a) the hard coating layer has at least two layers, namely a lower layer directly contacting the outermost surface of the tool substrate and an upper layer directly contacting the lower layer, and the total average thickness of the hard coating layer is 0.6 to 21.0 μm; (b) the lower layer is made of a Ti nitride or carbonitride and has an average layer thickness of 0.05 to 2.0 μm; (c) the upper layer is a composite nitride layer or a composite carbonitride layer of Al and Ti, and the average layer thickness is 0.5 to 20.0 μm; Composition formula: (Al X Ti 1-X ) (C Y N 1-Y ) the average content ratio X of Al to the total amount of Ti and Al in the composite nitride layer or the composite carbonitride layer avg and an average content ratio Y of C to the total amount of C and N in the composite nitride layer or the composite carbonitride layer. avg (However, X avg , Y avg are atomic ratios), and 0.70≦X avg ≦0.90, 0≦Y avg <0.05 and is made of a composite nitride layer or a composite carbonitride layer having a NaCl type face-centered cubic structure, (d) When the residual stress on the flank of the cutting edge of the tungsten carbide based cemented carbide of the surface-coated tool is S1 and the residual stress on the rake face of the cutting edge is S2, α) S1>S2 β) S2≦-200MPa γ) The absolute value of the difference between S1 and S2 is greater than 250 MPa A surface-coated cutting tool characterized by satisfying each of the above requirements.
2. When X-ray diffraction was performed on the upper layer, the ratio of the diffraction intensity value of the cubic (111) plane to the diffraction intensity value of the cubic (200) plane, I(111) / I(200), was:
2. The surface-coated cutting tool according to claim 1, wherein the relationship: 1.0≦I(111) / I(200) is satisfied.
3. When the residual stress on the flank of the cutting edge of the tungsten carbide based cemented carbide of the surface-coated tool is S1 and the residual stress on the rake face of the cutting edge is S2, α) S1>S2 β) S2≦-850MPa γ) The absolute value of the difference between S1 and S2 is greater than 500 MPa 3. The surface-coated cutting tool according to claim 1 or 2, which satisfies the above requirements.
Citation Information
Patent Citations
Surface-coated tungsten carbide base cemented carbide cutting tool excellent in wear-resistance and breakage-resistance
JP1994055311A
Method of manufacturing cutting insert formed of surface-coated titanium carbonitride based cermet
JP2012055976A
Surface-coated cutting tool and method of manufacturing the same
JP2017124463A
Tools with tialn coating
JP2018522748A
Surface-coated cutting tool excellent in defect resistance
JP2020157457A